Trilateral defence cooperation in the North: an assessment of interoperability between Norway, Sweden and Finland. Issue 3 (3rd July 2019) - Møller, Joakim Erma
ABSTRACT: Norway, Sweden and Finland have proclaimed a willingness to cooperate militarily in a future crisis or conflict despite their diverging alliance affiliation. This article assesses their ability to do so through various elements affecting their interoperability, with Arctic Challenge, a multinational military exercise, as an empirical basis. The analysis finds that the NATO/non-NATO-divide has a negative impact on the trilateral defence cooperation, especially on exchange of information and aspects related to command and control. At the same time, Finland and Sweden have become largely NATO-standardized through their active partnership with the Alliance. This has affected interoperability aspects, such as communication, culture, and the compatibility of technical solutions, in a positive manner. Through agreements with the Alliance, as well as domestic legal changes, the two NATO-partners have facilitated receiving military assistance from Norway and other NATO-members during a crisis. Other agreements between the Nordic countries, however, have been limited to peacetime.